EFEKTIVITAS PENGGUNAAN MEDIA ANIMASI PADA PEMBELAJARAN BAHASA INDONESIA DI MADRASAH IBTIDAIYAH - Muhammad Aziz Habibi; Khadijah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of using 2D animation media in Indonesian Language learning, particularly on narrative text material, in class IV-A of MIS Muhammadiyah Blangpidie. The problem underlying this research is the low average score of students' Indonesian Language subject (65) and the reliance on conventional learning media such as printed books and whiteboards, which resulted in one-way learning with limited active student engagement. This research employed a quantitative approach with a pre-experimental design in the form of a one-group pretest-posttest design. The population consisted of 20 students of class IV-A, determined through a saturated sampling technique. Of these, 2 students were absent, resulting in complete data from 18 students being analyzed. The research instrument was an essay test that had been tested for validity and reliability. Data were analyzed using the Shapiro-Wilk normality test, the Wilcoxon Signed-Rank Test for hypothesis testing, and the N-Gain test with the assistance of SPSS Statistics version 23. The results showed an average pretest score of 53.56 and an average posttest score of 72.06. The normality test indicated that the posttest data were not normally distributed (Sig. 0.008), so the Wilcoxon Signed-Rank Test was applied, yielding an Asymp. Sig. (2-tailed) value of 0.000 (< 0.05), meaning H0 was rejected and Ha was accepted. The N-Gain analysis showed an average value of 0.4349, categorized as moderate. Thus, it can be concluded that animation media has a significant effect on improving students' learning outcomes in comprehending narrative texts in Indonesian Language learning.